Study on the treatment of petrochemical industrial wastewater by EGSB-SBR-ozone oxidation combined process - ZHAO Fan; GONG Qian; HAN Yanhe; GUO Zhi; JI Hua; MA Xuejiao (Gongye shui chuli)
Petrochemical industrial wastewater, due to its high COD concentration, toxic and difficult to degrade substances and complex composition, may cause serious harm to the ecological environment, water safety and human health, which requires effective treatment before discharge. A EGSB-SBR-ozone oxidation combined proceess was constructed to investigate its effect on the treatment of mixed water produced by a petrochemical enterprise with SAR concentration condensate, RO concentrate, maleic anhydride wastewater and PPG wastewater. The results showed that in anaerobic treatment, the EGSB process was more effective in treating this mixed water, and the volumetric loading (in terms of COD) could reach about 5 kg/(m3·d) when the influent COD was 4 000-9 000 mg/L. The COD removal rate could be stabilized at more than 80%, and the CH4 production rate (in terms of the standard volume of CH4 produced by consuming a unit of COD) could be up to 300 mL/g. The effluent from the anaerobic process was further treated by aerobic SBR process, which resulted in an average COD removal rate of more than 80%, with a maximum sludge load of 0.22 kg/(kg·d). The aerobic SBR effluent was treated in depth by ozone oxidation process with the ozone dosing ratio of 3.6 or less, and the average COD removal rate reached 60%. EGSB-SBR-ozone oxidation combined process had a better effect on the treatment of target mixed wastewater. In the actual project, the effluent could meet the secondary standard of Pollutant Emission Standards for Urban Wastewater Treatment Plants (GB 18918-2002) after further treatment by subsequent adsorption and high salt biofilter process.